PTU-014 Endoscopic muscosal resection of large coloerectal polyps in a district general hospital- is it safe and efficient?. (22nd June 2015) - El-Sayed, C; McArdle, K; Chauhan, V; Cheung, M; Osborne, M
Abstract : Introduction: Colorectal cancer is the third most common cancer in the UK. Most colorectal cancers are believed to arise secondary to adenomatous polyps. The removal of adenomas through endoscopy has thus reduced the incidence of colorectal cancer. Endoscopic mucosal resection (EMR) is currently the preferred method for removal of large polyps as it is safe and efficient. We conducted a study to investigate the efficiency of developing a dedicated large polyp colonoscopy list in a District General Hospital (DGH). Method: All patients undergoing endoscopic removal of polyps by a single surgeon between May 2012 and December 2014 at Warwick Hospital were included in the study. Polyps measuring 1 cm and above were identified as large polyps. The average size of the polyps resected was 2.7 cm. Data collected included patients' demographics, Paris score, complications and readmission rate related to the procedure. Outcomes were analysed retrospectively using SPSS version 22. Results: Eighty-three patients were included in the study with a mean age of seventy-one years old. The average polyp size was 2.7 cm. Histology revealed 72% of specimens were TVA (tubule villous adenoma) and 0.02% were malignant requiring surgical resection. The majority of polyps were removed using EMR (80.7%). Complete resection was achieved in 69 (84%) of patients. Few patients were re-admitted following the procedure (0.06%) due to complications related to bleeding. No perforations occurred. Conclusion: A dedicated large polyp endoscopy list can be performed in a DGH by an experienced endoscopist with minimal complications and readmissions. Disclosure of interest: None Declared.